Parental stress in parents of young children : effect from social support, social media usage and gender difference - Nanna Huld Kristjánsdóttir 1997- (2020)
The aim of this study is to examine parental stress in parents of young children in Iceland. Previous studies have mainly examined mothers and studies on the matter are getting old considering today’s society and technology. The main purpose of this current study is to see if there is a gender difference on parental stress in Iceland like majority of previous research studies have concluded. As well as if social support and communication through social media have a positive effect on parental stress and if time spent on social media has a negative effect on parental stress. A survey was submitted to participants of children at the ages between 1-6 years old. Participants were 120, 88 women and 32 men. The age ranged from 20 to 50 years and older. A multivariate regression was conducted to see if social support and social media usage had an effect on parental stress. The results showed no significant effect from the gender, social support or social media hypotheses nor how much time people spent on social media, on parental stress. Although, a significant positive effect was found by comparing oneself to other parents online on parental stress. Meaning, comparison increases parental stress. Keywords: Parental stress, social support, social media, social comparison Markmið þessarar rannsóknar er að skoða foreldrastreitu hjá foreldrum ungra barna á Íslandi. Fyrri rannsóknir hafa aðallega skoðað mæður en rannsóknir á foreldrastreitu eru að verða gamlar miðað við samfélagið og tæknina í dag. Það sem þessi rannsókn kannar er hvort sami kynjamunur á foreldrastreitu sé til staðar á Íslandi og aðrar rannsóknir hafa sýnt fram á. Einnig hvort félagslegur stuðningur hafi áhrif á streitu og hvort samskipti á samfélagsmiðlum geti verið jákvæð ásamt því að kanna hvort það að eyða meiri tíma á samfélagsmiðlum hafi neikvæð áhrif á foreldrastreitu. Netkönnun var lögð fyrir þátttakendur sem áttu börn á aldrinum 1-6 ára. Þátttakendur voru 120 talsins, 88 konur og 32 karlar á aldrinum 20 til 50 ára og eldri. Margvíð ...